Nothing is Lost, Nothing is Created, Everything is Translated. The Material Mechanics Tale in Smart Working Practices - Nesi Lammardo, Marika (E|C, 2023)
This paper examines the relationship between material engineers and management sciences from a socio-semiotics point of view. More precisely, the analysis proposed suggests a hypothesis of the link between flexibility, and resilience mechanical proprieties, and workforce management theories. For this purpose: 1) we investigate flexibility and resilience as ‘technical cores’ in the enunciative praxis; 2) we propose an intersemiotics translation model based on E. Goffman, M. Minsky, and U. Eco’s theories to clarify their conversion in managerial policies; 3) we show intersemiotics translation defines a semi-parabolic system aiming to report on a specific form of life. Along these lines, we discuss examples related to the Smart Working manufacturing system literature review.